Traditions & encounters : - Bentley, Jerry H. (McGraw-Hill, 2006)
Over a million students at thousands of schools have learned about world history with the best selling book for the course, Traditions and Encounters: A Global Perspective on the Past. Using the twin themes of traditions and encounters, the text emphasizes both the distinctive patterns of historical development within individual societies and the profound results of interactions between different societies. Exploring the historical record of cross-cultural interactions and exchanges, Traditions and Encounters places the world of contemporary globalization in historical context. The book helps students understand the worlds major societies and shows how the interactions of these societies affect history throughout the world. The authors tell a coherent and digestible story of the past that is not weighed down by excessive detail, so instructors are able to incorporate additional readings. This edition provides an updated map program as well as the latest scholarship. It also moves Primary Source Investigator online, improving access for students to work with primary sources